2001
DOI: 10.1021/ol0168364
|View full text |Cite
|
Sign up to set email alerts
|

A Stereoselective Synthesis of the C10−C31 (BCDEF Ring) Portion of Pinnatoxin A

Abstract: [reaction: see text] An efficient synthesis of the C10-C31 (BCDEF ring) portion of pinnatoxin A has been achieved. The key step is a highly stereoselective construction of the dispiroketal (BCD ring) system employing an intramolecular hetero-Michael reaction of a reversibly formed hemiketal alkoxide through the use of LiOMe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…This spiroacetalization has been elegantly pioneered by Kishi and then by Inoue–Hirama, Nakamura–Hashimoto, and Zakarian in their respective total syntheses of pinnatoxin ( 1 ), as well as by Ishihara et al in their preparation of the bis-spiroacetal core of spirolide B . The 1,4-diketone motif may be constructed by a number of ways, often requiring several steps .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This spiroacetalization has been elegantly pioneered by Kishi and then by Inoue–Hirama, Nakamura–Hashimoto, and Zakarian in their respective total syntheses of pinnatoxin ( 1 ), as well as by Ishihara et al in their preparation of the bis-spiroacetal core of spirolide B . The 1,4-diketone motif may be constructed by a number of ways, often requiring several steps .…”
mentioning
confidence: 99%
“…It is noteworthy that substitution on the carbon chain is allowed on both partners, but α-substitution in acylsilane was shown to slow down the process, leading to lower yields . Removal of the tert -butyldimethylsilyl protecting group was then carried out under standard acidic conditions, leading to a spontaneous cyclization, producing the desired bis-spiroacetals in moderate to good yields as a mixture of diastereomers (dr estimated using both 1 H NMR and GC–MS) (Scheme ) . Various acidic conditions were tested (TfOH, HCl, MgBr 2 , BF 3 ·OEt 2 , TMSOTf, Sc(OTf) 3 ), but camphorsulfonic acid (CSA) in CH 3 CN at room temperature was found to be optimal in terms of yields.…”
mentioning
confidence: 99%
“…These results suggest that the synthesized cisoidal bisspiroacetal product is only sustainable under weakly acidic conditions. Nevertheless, synthetic studies of pinnatoxin have demonstrated that cisoidal 6,5,6‐bisspiroacetal intermediates tolerate strongly basic reagents, such as t BuLi, potassium bis(trimethylsilyl)amide and Grignard reagents, and harsh conditions, such as Diels–Alder reactions (160 °C for 12 h in p ‐xylene) . These examples show that further chemical conversion from a cisoidal bisspiroacetal product is feasible, which means the Mg‐mediated isomerization established here could be incorporated into a synthetic strategy for bisspiroacetal‐containing natural products.…”
Section: Figurementioning
confidence: 84%
“…In another synthetic approach published by Hashimoto et al, the crucial bicyclic acetal 150 of (-)-pinnatoxin A (1) [41] was synthesized using CSA in dichloromethane from the bis-spiroacetal 149, which was in turn prepared from 148 (Scheme 28).…”
Section: Synthesis Of Bridged [321] and [221] Acetalsmentioning
confidence: 99%